Room-temperature fast self-healing graphene polyurethane network with high robustness and ductility through biomimetic interface structures - Hao Wu; Jinqiu Tao; Junhao Xie; Chengbao Liu; Qianping Ran (Nano Materials Science, 2025)
Intelligent polymers have garnered significant attention for enhancing component safety, but there are still obstacles to achieving rapid self-healing at room temperature. Here, inspired by the microscopic layered structure of mother-of-pearl, we have developed a biomimetic composite with high strength and self-repairing capabilities, achieved by the ordered arrangement of pearl-like structures within a flexible polyurethane matrix and GO nanosheets functionalized by in situ polymerization of carbon dots (CDs), this biomimetic interface design approach results in a material strength of 8 ​MPa and toughness (162 ​MJ ​m−3), exceptional ductile properties (2697 ​% elongation at break), and a world-record the fast and high-efficient self-healing ability at room temperature (96 ​% at 25 ​°C for 60 ​min). Thereby these composites overcome the limitations of dynamic composite networks of graphene that struggle to balance repair capability and robustness, and the CDs in situ loaded in the interfacial layer inhibit corrosion and prevent damage to the metal substrate during the repair process. (The Ƶ f=0.01Hz was 1.81 ​× ​109 ​Ω ​cm2 after 2 ​h of healing). Besides, the material can be intelligently actuated and shape memory repaired, which provides reliable protection for developments in smart and flexible devices such as robots and electronic skins.